Beings and beasts: Human-animal relations at the margins - Aiyadural, Ambika; Ingole, Prashant (New Delhi Cambridge University Press, 2025)
While, a lot has been written about the need to 'decolonize' animal studies and wildlife conservation, there is no discussion or attempt to 'de-brahminize' animal studies and conservation science in India. Similarly, some animals and birds are positioned as superior in the Brahmanical social order, others seem to be subordinated and are associated with certain 'inferior' caste groups. Beings and Beasts discusses the relations between humans and animals of marginalized societies, especially of Dalits and Tribals.